Persepsi Penerapan Fitoremediasi melalui Taman Tematik Akuatik di Kebun Raya Purwodadi - Rony Irawanto; Emilia Anjar Prastiwi (Universitas Sebelas Maret, 2019)
This paper aims to find out the point of view and suggestion for the application of the phytoremediation roles in the thematic garden of Purwodadi Botanic Gardens by research staff as an effort to conserve plants. This study uses a qualitative research approach. Data obtained through interviews with 16 (sixteen) informants. The sampling technique used was purposive sampling. Data collection techniques in this study through in-depth interviews. Processing data from interviews by documenting transcripts. This study produced two propositions: the scientific advice and the point of views from researchers with different fields about the function of aquatic thematic collection that are used as applications for environmental phytoremediation.